Biological characterization and toxicity analysis of ethanolic banana (Musa paradisiaca L.) flower extract as antimicrobial for cherry tomato - Ahmed Mohamed Mousa, Khadija (2022)
Food products can be subjected to contamination by bacteria and fungi. The growth of pathogenic bacteria in food products caused foodborne illnesses resulting consumption of contaminated food. Food spoilage bacteria, yeast, and mold may contribute to the deterioration of the color, texture, and flavor of food. To overcome this problem, prevention should be done at the early stage of food processing such as sanitizing. Commonly, chemical sanitizers had been applied in the food industry. However, applications of these chemicals in long term will affect human health. Therefore, developments of natural sanitizers derived from plant sources are gaining more attention nowadays. In this study, the antimicrobial activity of the ethanolic extract of banana flowers against foodborne pathogens and food spoilage microorganisms was conducted. The antimicrobial analysis includes Disc Diffusion Assay (DDA), Minimum Inhibition Concentration (MIC), Minimum Bactericidal Concentration (MBC), Minimum Fungicidal Concentration (MFC), and Time kill curve. Other tests were phytochemicals analysis Gas Chromatograph Mass Spectra (GC-MS) and Liquid Chromatograph Mass Spectra (LC-MS), toxicity test using brine shrimp lethality assays, and application of an ethanolic extract of banana flower on microbial population in cherry tomato. The susceptibility test showed that all tested pathogenic bacteria were inhibited by ethanolic extract of banana flower, with the range of inhibition zone between 8.83 ± 0.29 to 10.67 ± 0.29 mm. The ethanolic extract was significantly effective against Bacillus subtilus ATCC6633 with an inhibition zone of 10.67 ± 0.29 mm. The MICs values of the extract against all tested bacteria strains ranged between 3.13 to 6.25 mg/mL. Ethanolic extract was highly effective against Escherichia coli ATCC43895, B. subtilis ATCC6633, B. pumilus ATCC14884, and Proteus mirabilis ATCC21100 with a MIC of 3.13mg/ml. On the other hand, the MBC values ranged between 6.25 to 25 mg/mL. E. coli ATCC43895 was the most susceptible bacteria with an MBC value of 6.25 mg/mL. The time-kill curve study showed that E. coli was found to be completely killed after exposure to the ethanolic extract of banana flower at 4× MIC after 2 h of incubation time. However, the population of Klebsiella pneumoniae ATCC13773, B. pumilus ATCC14884, B. subtilus ATCC6633, B. megaterium ATCC14581, and P. mirabilis ATCC21100 were reduced to less than 3 log CFU/mL once treated with the ethanolic extract of banana flower at 4× MIC for 4 h. Moreover, the antifungal activity of the ethanolic extract of banana flower in terms of inhibition zone against Aspergillus niger ATCC9029, Rhizopus oligosporus ATCC22959, Rhizopus oryzae ATCC22580, and Candida spp. (Candida albicans ATCC10231, Candida krusei ATCC32196, and Candida parapsilosis ATCC22019) ranged between 6.13 ± 0.06 to 9.67 ± 0.62 mm. The MIC values were 6.5 to 12.5 mg/mL while the MFC values were 12.5 to 25 mg/mL. The time-kill curve result for C. albicans was found to be killed completely at 4× MIC for 4 hr of exposure time, while C. krusei and C. parapsilosis were found to be reduced to less than 3 log10 CFU/mL after exposure to the extract at 4× MIC for 4 h. In inhibition of conidia germination, qualitative analysis of all the tested fungi species showed no growth after being treated with extract started at 2× MIC and 4 × MIC for 14 days. Whereas the quantitative analysis using 4× MIC values for 48 h showed that the percentage of conidia germinations were completely inhibited for Rh. oligosporus at 2× MIC and 1× MIC for Asp. niger and Rh. oryzae. Cell constituents release analysis; crystal violet assay showed altering in cell wall linearity, cells ruptured, and leakage of the cytoplasm. Generally, the antimicrobial activity of the ethanolic extract of the banana flower was not affected by different pHs and temperatures. The identified bioactive compounds in the ethanolic extract of the banana flower by using GC-MS were hexadecenoic acid, 1- heptacosanol, 1- heneicosanol, 17-Pentatriacontene, diacetone alcohol, diisooctyl phthalate, fucosterol, heptadecanol, octadecane, octadecanoic acid, methyl ester, phenol, 2,4-bis(1,1- dimethylethyl)- (CAS) 2,4-Di-tert-butylphenol, squalene, and triacontane. The identified bioactive compounds by using LC-MS included hippeastrine, L-(-)-carvone, 4- hydroxybenzaldehyde, and vanillin. The toxicity study demonstrated that the ethanolic extract of the banana flower was not toxic with LC50 = 4.1993 mg/mL. Ethanolic extract of banana flower had been used in the washing treatment of cherry tomato at different concentrations of 0.05 %, 0.50%, 0.25%, and 5.00% with an exposure time of 5 min and 15 min. For the storage study, the treated samples were kept at 4°C and 25 ± 2°C for 21 days. TPC, yeast, and mold start to reduce when treated with 0.05% and 0.25% concentrations of the extract with an exposure time of 5 and 15 min as compared to tap water treatment. Significant reduction of the microorganism was observed at 5.00% concentration with 5 min and 15 min exposure time. In the storage study, E. coli was not detected at 4˚C and 25 ± 2˚C in control and treated samples starting from day 0 until the 21 days. This means that E. coli was not detected on the cherry tomato samples before starting with washing treatment. TPC and yeast and mold populations from the samples kept at 4˚C and 25 ± 2˚C showed greater reduction up to less than 3 Log CFU/mL in all treated samples. There is no previous study of ethanolic M. paradisiaca L. flower extract on food spoilage microorganisms, it is best to assess the antifungal action of the extract against more food spoilage fungi, including yeast and filamentous fungi. This is first study of Four bioactive compounds identified by LC-MS and detected of M. paradisiaca L. flower extract was hippeastrine, L-(-)-Carvone, 4-Hydroxybenzaldehyde, and Vanillin. In conclusion, the ethanolic extract of banana flowers exhibited antimicrobial activity, thus it can be developed as a natural sanitizer for washing raw food materials and preventing food spoilage during storage.